Social retfærdighed og økonomiske incitamenter: Om systemkritik og moraliseren i venstreorienteret politisk teori - Rostbøll, Christian F. (Politik, 2013)
The Danish left is split between its commitment to equality and its relationship to the working class. e current center-left government has made reforms that accept the necessity of giving economic incentives for working, which increases inequality. e article argues that the left needs to clarify its normative commit- ments and considers the potential contribution of normative political theory to such a clari cation. Particu- larly, the article presents and discusses G.A. Cohens critique of the incentives argument and the need for an egalitarian ethos.